2016
DOI: 10.1111/imm.12596
|View full text |Cite
|
Sign up to set email alerts
|

Critical role of CCL22/CCR4 axis in the maintenance of immune homeostasis during apoptotic cell clearance by splenic CD8α+CD103+ dendritic cells

Abstract: SummaryMacrophages and dendritic cells (DCs) in murine spleen are essential for the maintenance of immune homeostasis by elimination of blood-borne foreign particles and organisms. It has been reported that splenic DCs, especially CD8a + CD103 + DCs, are responsible for tolerance to apoptosis-associated antigens. However, the molecular mechanism by which these DCs maintain immune homeostasis by blood-borne apoptotic cell clearance remains elusive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
13
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 46 publications
2
13
0
Order By: Relevance
“…1 E). This is consistent with previous data comparing chemokine expression profiles in splenic and lymph node DCs (Vitali et al, 2012; Hao et al, 2016) and fits with transcriptional data from the ImmGen database. In vitro, CCL22 is secreted by both CD11c + DCs that are obtained from freshly isolated lymphoid tissue and by bone marrow–derived DCs (BMDCs) that are generated by culture in the presence of IL-4 and GM-CSF.…”
Section: Resultssupporting
confidence: 92%
“…1 E). This is consistent with previous data comparing chemokine expression profiles in splenic and lymph node DCs (Vitali et al, 2012; Hao et al, 2016) and fits with transcriptional data from the ImmGen database. In vitro, CCL22 is secreted by both CD11c + DCs that are obtained from freshly isolated lymphoid tissue and by bone marrow–derived DCs (BMDCs) that are generated by culture in the presence of IL-4 and GM-CSF.…”
Section: Resultssupporting
confidence: 92%
“…Primers for β-Actin and Ahr were custom designed with the following sequences: Act Forward (5′-AGATGACCCAGATCATGTTTGAG-3′); Act Reverse (5′- AGGTCCAGACGCAGGATG-3′); Ahr Forward (5′-AGGATCGGGGTACCAGTTCA-3′); Ahr Reverse (5′-CTCCAGCGACTGTGTTTTGC-3′); Il6 Forward (5′-GCCTTCTTGGGACTGATGCT-3′); Il6 Reverse (5′-TGCCATTGCACAACTCTTTTC-3′); Il5ra Forward (5′-GGTCCCGGTATGCAGTTCTA-3′); Il5ra Reverse 5′-AGCCGAATGCTGGAAAAGTG-3′. Ccl22 (Hao et al., 2016), Ebi3 (Shen et al., 2014), Il2 (Martins et al., 2008), Il10 (Yanaba et al., 2009), p35 (Shen et al., 2014) Tnf (Denaës et al., 2016) were used as previously described. qPCR data were calculated as the ratio of gene to β- Actin expression by the relative quantification method (ΔΔC t ; means ± s.e.m.…”
Section: Methodsmentioning
confidence: 99%
“…The induction of tolerance was dependent on both CD169 + macrophages and CCR4 ( 129 ). In contrast, another study reported that CCL22 is produced by the cDC1s upon injection with apoptotic cells, showing that the role of the cell type that produces CCL22 remains to be clarified ( 130 ). However, together these studies indicate that marginal zone CD169 + macrophages and cDC1s are essential in the induction of tolerance via the uptake of apoptotic cells and suggest a functional collaboration in this process.…”
Section: Cd169 + Macrophages Efficiently Capture Pmentioning
confidence: 99%